BUILDING MATERIALS FOR THERMAL PERFORMANCE RETROFITTING OF AN OFFICE BUILDING SKIN UNDER CONTINENTAL MEDITERRANEAN CLIMATE - Djebaili, I. A.; Rouag Saffidine, D.; Sotehi, O. (Journal of Fundamental and Applied Sciences, 2019)
In the context of optimizing the buildings energy consumption, the improvement of the parameters of nonperforming building skins may allow a greater energy efficiency and optimize indoor comfort conditions. This is greatly function of the building envelope construction materials characteristics. In effects, the building skin may contain weak points for heat exchange due to poor or missing insulation, provoking significant energy loss. To meet to such a problem, retrofitting strategy can be adopted for reducing energy loss in existing buildings through appropriate materials. For this study, the thermal behavior and envelop performance of an office building was investigated by means of infrared thermography. This provided clear evidence of thermal leaks. Subsequently, a numerical simulation was carried out using TRNSYS software in order compare the cooling and heating needs, first, at actual building, and then after applying a Rockwool external insulation together with energetic performant windows. The results show 28% of energy savings.